Pengaruh Karakteristik Individu dan Beban Kerja Terhadap Kinerja Pegawai: (Studi Pada Tenaga Kependidikan Universitas Galuh Ciamis) - Sarah Kartika Sari; Enas Enas; Apri Budianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The problems faced in this study include (1) How do individual characteristics affect employee performance in the Education Personnel of Galuh Ciamis University? (2) How does workload affect employee performance in the Education Personnel of Galuh Ciamis University? (3) How do individual characteristics and workload affect employee performance in the Education Personnel of Galuh Ciamis University? This study aims to study, find out, and analyze (1) The effect of individual characteristics on employee performance in the Education Personnel of Galuh Ciamis University. (2) The effect of workload on employee performance in the Education Personnel of Galuh Ciamis University. (3) The effect of individual characteristics and workload on employee performance in the Education Personnel of Galuh Ciamis University. The method used in this study is an explanatory survey, while the technical data analysis, namely validity test, reliability test, descriptive statistics, Inductive Statistical Analysis (Inferential) with Multiple Regression. The results of the study inform that (1) Individual characteristics have a positive effect on employee performance in the Galuh Ciamis University Education Staff. This means that if individual characteristics are improved, then employee performance in the Galuh Ciamis University Education Staff will also increase. (2) Workload has a positive effect on employee performance in the Galuh Ciamis University Education Staff. This means that if the workload is increased, then employee performance in the Galuh Ciamis University Education Staff will also increase. (3) Individual characteristics and workload have a positive effect on employee performance in the Galuh Ciamis University Education Staff. This means that if individual characteristics and workload are improved, then employee performance in the Galuh Ciamis University Education Staff will also increase.